2023
DOI: 10.3390/agronomy13112831
|View full text |Cite
|
Sign up to set email alerts
|

The Differentiations in the Soil Nematode Community in an Agricultural Field after Soil Amendment Using Composted Coffee Waste in Various Concentrations

Panagiotis Kekelis,
Maria D. Argyropoulou,
Aphrodite Theofilidou
et al.

Abstract: In a field experiment, composted coffee waste (CW) was used as soil amendment at three different rates (2%, 4%, and 8%) in plots cultivated with wheat; the effects on the soil nematode community and plant growth were studied. By sampling twice, i.e., three and six months after the application of treatments (3MAA and 6MAA), the duration of these effects was also evaluated. Treatment using composted coffee waste (CW) led to an increased abundance of all soil nematodes, especially of bacterivores and fungivores, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…This resulted in slower decomposition by microorganisms and an increased dominance of fungivores in the long term. These findings differ from those recorded after the incorporation of other types of organic amendments with high C/N ratios in the soil system, which typically increase bacterial populations, causing a spike in bacterivorous nematodes [41,42]. Several studies reported increased fungal populations and fungal/bacterial ratios in OMW-amended soils, suggesting that OMW serves as a suitable substrate for fungi [36,[43][44][45][46] and thus explaining the dominance of fungivores post-OMW addition.…”
Section: Effect On Nematode Abundance Community Composition and Gener...mentioning
confidence: 68%
“…This resulted in slower decomposition by microorganisms and an increased dominance of fungivores in the long term. These findings differ from those recorded after the incorporation of other types of organic amendments with high C/N ratios in the soil system, which typically increase bacterial populations, causing a spike in bacterivorous nematodes [41,42]. Several studies reported increased fungal populations and fungal/bacterial ratios in OMW-amended soils, suggesting that OMW serves as a suitable substrate for fungi [36,[43][44][45][46] and thus explaining the dominance of fungivores post-OMW addition.…”
Section: Effect On Nematode Abundance Community Composition and Gener...mentioning
confidence: 68%
“…The current results from the dry weight analysis clearly show that the fertilizer type significantly influences the dry weight of red radish plants. Much research has proved the effect of SCGs and VC on plant measurements such as weight, length, leaf development, surface area, and soil properties [7,8,37,39,41].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, certain studies have indicated that these compounds are accountable for the chelating characteristics of SCGs, thereby rendering their removal inadvisable. Research has also investigated the utilization of SCGs as bio-chelates, resulting in a combination of waste material and micronutrients that can be used to enhance the nutritional value of edible plants through biofortification [7,8,37,41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of SCG has experienced a significant increase in popularity in recent years, primarily because it contains a high concentration of organic compounds such as fatty acids, lignin, cellulose, hemicellulose, and other polysaccharides. Studies have been undertaken to explore its potential application in improving soil fertility and increasing agricultural productivity [8].…”
Section: Introductionmentioning
confidence: 99%